2008
DOI: 10.1038/leu.2008.74
|View full text |Cite
|
Sign up to set email alerts
|

Effective killing of Gleevec-resistant CML cells with T315I mutation by a natural compound PEITC through redox-mediated mechanism

Abstract: Mutation of Bcr-Abl is an important mechanism by which chronic myelogenous leukemia (CML) cells become resistant to Gleevec. The T315I mutation is clinically significant since CML cells harboring this mutation are insensitive to Gleevec and other Bcr-Abl-targeted drugs. Identification of new agents capable of effectively killing CML cells with T315I mutation would have important therapeutic implications in Gleevecresistant CML. Here, we showed that b-phenylethyl isothiocyanate (PEITC), a natural compound found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 35 publications
(47 reference statements)
3
84
0
Order By: Relevance
“…Growth inhibitory effects of ITCs may involve direct conjugation and functional modification of key cell regulatory proteins and/or via increased ROS production following depletion of intracellular GSH [25,31,68]. ROS generally promote activation of HIF [41][42][43][44][45][46][47] and consistent with this, we demonstrated that NAC and catalase decreased induction of HIF activity in hypoxic conditions.…”
Section: Inhibition Of Hif Activity By Peitc Is Independent Of Prolylsupporting
confidence: 70%
See 1 more Smart Citation
“…Growth inhibitory effects of ITCs may involve direct conjugation and functional modification of key cell regulatory proteins and/or via increased ROS production following depletion of intracellular GSH [25,31,68]. ROS generally promote activation of HIF [41][42][43][44][45][46][47] and consistent with this, we demonstrated that NAC and catalase decreased induction of HIF activity in hypoxic conditions.…”
Section: Inhibition Of Hif Activity By Peitc Is Independent Of Prolylsupporting
confidence: 70%
“…Enhancing cellular GSH levels by treatment with GSH or its metabolic precursor NAC can interfere with PEITC-induced growth inhibition [25,31,68]. Thus, we wanted to determine whether NAC also interfered with inhibition of HIF activity by PEITC.…”
Section: 6mentioning
confidence: 99%
“…We reason that modulating gemcitabineinduced redox regulatory mechanisms by reducing GSH pool may affect cell survival and drug sensitivity. PEITC, a novel compound that has been reported to deplete GSH and subsequently elevate oxidative stress (15,17), may circumvent such protection and enhance the antipancreatic cancer activity of gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…b-Phenylethyl isothiocyanate (PEITC), a natural compound found in cruciferous vegetables, depletes GSH and selectively kills cancer cells while sparing healthy cells (14)(15)(16)(17). Given the fact that stimulation of ROS is generated by gemcitabine in PDAC cells, we hypothesized that the cells increase cellular GSH to prevent oxidative damage and that PEITC enhances the effect of gemcitabine-induced ROS through the redox modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Rakshit et al (2010) reported the role of ROS in chlorogenic acid (Chi)-induced cell death in CML cell lines as well as primary leukemia cells from CML patients. In addition, Zhang et al (2008) reported that beta-phenylethyl isothiocyanate (PEITC) exerted the cytotoxic effect in Glivec-resistant CML cells by regulating redox signaling. These evidences suggest the potential of natural products for CML treatment.…”
Section: Discussionmentioning
confidence: 99%